The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3758/s13415-018-0586-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk seeking for losses modulates the functional connectivity of the default mode and left frontoparietal networks in young males

Abstract: Value-based decision making (VBDM) is a principle that states that humans and other species adapt their behavior according to the dynamic subjective values of the chosen or unchosen options. The neural bases of this process have been extensively investigated using task-based fMRI and lesion studies. However, the growing field of resting-state functional connectivity (RSFC) may shed light on the organization and function of brain connections across different decision-making domains. With this aim, we used indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 89 publications
(100 reference statements)
1
5
0
Order By: Relevance
“…The latter further split into a risk taking for gains and mixed gambles cluster and a sampling bias cluster. The factor structure, as well as the clustering, are broadly consistent with theoretical predictions of a cognitive control dimension separate from a decision-making dimension that segregates gain and loss contexts (Deza Araujo et al, 2018).…”
Section: Split-half Reliabilitysupporting
confidence: 74%
See 1 more Smart Citation
“…The latter further split into a risk taking for gains and mixed gambles cluster and a sampling bias cluster. The factor structure, as well as the clustering, are broadly consistent with theoretical predictions of a cognitive control dimension separate from a decision-making dimension that segregates gain and loss contexts (Deza Araujo et al, 2018).…”
Section: Split-half Reliabilitysupporting
confidence: 74%
“…In a recent historical review, Nigg (2017) concluded that most theories include working memory and inhibition in cognitive control (see also Botvinik & Braver, 2015), but separate them from decision-making such as risk taking. Furthermore, empirical evidence shows a distinction in neural circuits underlying risk taking to avoid losses and risk taking for gains (Deza Araujo et al, 2018). Risk taking for gains decreases with age, putatively reflecting decreases in dopamine (Rutledge et al, 2016), and risk taking for losses has been linked to circadian rhythms (Bedder et al, 2020).…”
Section: Construct Validitymentioning
confidence: 99%
“…Comparing risky with nonrisky adolescents, DeWitt, Aslan, and Filbey (2014) observed that the former group displayed increased connectivity between the amygdala and the right MFG, left cingulate gyrus, left precuneus, and right inferior parietal cortex and between the nucleus accumbens and the right MFG. In a similar vein, Deza Araujo et al (2018) demonstrated hyperconnectivity between the frontoparietal network and the occipital cortex and between the DMN and medial temporal and frontal regions in high risk-seeking behavior in losses (observed in people who prefer delayed potential high losses rather than immediate but sure small losses).…”
Section: Introductionmentioning
confidence: 76%
“…Other research work conducted by Araujo et al (2018) discussed the distinct connectivity patterns of large-scale brain networks that may underlie individual differences in decision-making in healthy populations. Results showed that higher risk seeking for losses was associated with increased connectivity between medial temporal regions, frontal regions, and the default mode network.…”
Section: Risk Seekingmentioning
confidence: 99%